The Added Value of Pathology Review in Vulvar Cancer: Results From a Population-based Cohort Study. (March 2017) - Barbera, Lisa; Gien, Lilian T.; Sutradhar, Rinku; Thomas, Gillian; Covens, Al; Elit, Laurie; Fyles, Anthony; Rakovitch, Eileen; Liu, Ying; Khalifa, Mahmoud
Abstract : We conducted a population-based patterns of care study of vulvar carcinoma. This paper describes the changes in reporting based on pathology review. This is a retrospective population-based cohort study. We obtained all pathology records available from the provincial cancer registry for primary invasive squamous cell carcinoma of the vulva diagnosed between 1998 and 2007. Pathology reviews were conducted centrally by a group of gynecologic pathologists and were identified during abstraction. Corresponding original reports were matched to pathology review reports based on accession numbers. We compared the reported value for presence/absence of invasion, grade, depth, thickness, size, lymphovascular space invasion, peripheral margin status, and deep margin status in the original and review report. A total of 1011 vulvar resection reports were identified. From these, we identified 316 pairs of original/review reports. Missing data were common but improved in the reviews. In total, 55 (17%) reports had at least 1 change from the original to the review based on presence of invasion, depth, lymphovascular space invasion, or margin. When we included reports where a variable was missing in the original but then completed in the review, there were clinically relevant changes in 210 reports (66%). Vulvar carcinoma is a rare diagnosis and pathology reviews resulted in potentially important clinical changes in a significant proportion of cases. Referral pathologists play an important role in contributing to high-quality clinical decisions.